Project management metrics, KPIs, and dashboards : a guide to measuring and monitoring project performance - Kerzner, Harold (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
The new edition of Harold Kerzner's bestselling book on measuring project management performance With today's complex projects, increased stakeholder involvement, and advances in computer technology, metrics and key performance indicators (KPIs) have become increasingly integral to informed decision-making and effective project management. Project Management Metrics, KPIs, and Dashboards, Second Edition helps functional managers gain a thorough grasp of what metrics and KPIs are and how to use them, as well as an understanding of different dashboard types, design issue.
3.2 Project Management Metrics: Current ViewMetrics and Small Companies; 3.3 Metrics Management Myths; 3.4 Selling Executives on a Metrics Management Program; 3.5 Understanding Metrics; 3.6 Causes for Lack of Support for Metrics Management; 3.7 Using Metrics in Employee Performance Reviews; 3.8 Characteristics of a Metric; 3.9 Metric Categories and Types; 3.10 Selecting the Metrics; 3.11 Selecting a Metric/KPI Owner; 3.12 Metrics and Information Systems; 3.13 Critical Success Factors; 3.14 Metrics and the PMO; 3.15 Metrics and Project Oversight/Governance; 3.16 Metric Traps.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Project management; Project management -- Quality control; Performance standards; Work measurement; Performance standards; Project management -- Quality control; Project management; Work measurement; BUSINESS & ECONOMICS -- Project Management; TECHNOLOGY & ENGINEERING -- Project Management; Projektmanagement; Electronic books; Electronic books